1981
DOI: 10.1159/000123257
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Dynorphin-(1–13) Immunoreactivity in Rat Neurointermediate Pituitaries Are Concomitantly Altered with Those of Leucine Enkephalin and Vasopressin in Response to Various Endocrine Manipulations

Abstract: The levels of dynorphin-(1-13), leucine enkephalin, β-endorphin and vasopressin immunoreactivity (ir-DYN, ir-1-ENK, ir-β-END, ir-VP) have been determined in the anterior and in the neurointermediate lobes of the pituitary of rats subjected to a variety of manipulations. Dehydration of rats by 5 days enforced imbibition of a 2% solution of NaCl resulted in a significant decrease in the levels of ir-DYN, ir-l-ENK and ir-VP, but not in those of ir-β-END in the neurointermediate lobe of the pituitary. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…If a change in axonal transport or release is indeed involved, altered metabo lism resulting from insulin deficiency may play a more prominent role than the lack of insulin per se. Increase in release from the NIL is a distinct possibility, at least for cholecystokinin, which is coreleased with vasopres sin [12] and fordynorphin, which is altered in content in the same way as vasopressin [35], because hyperosmolality in diabetes will un doubtedly lead to an increase in vasopressin release [33], If there is indeed an increase in the release of dynorphin and cholecystokinin from the NIL, the increased secretion of these neuropeptides and P-endorphin may stimu late insulin secretion from the 'residual' pan creatic islets in streptozotocin-treated rats, as a compensatory mechanism for the decrease in insulin secretion. Opioid peptides [36] and cholecystokinin [37] have been shown to be insulinotropic when administered peripher ally.…”
Section: Discussionmentioning
confidence: 99%
“…If a change in axonal transport or release is indeed involved, altered metabo lism resulting from insulin deficiency may play a more prominent role than the lack of insulin per se. Increase in release from the NIL is a distinct possibility, at least for cholecystokinin, which is coreleased with vasopres sin [12] and fordynorphin, which is altered in content in the same way as vasopressin [35], because hyperosmolality in diabetes will un doubtedly lead to an increase in vasopressin release [33], If there is indeed an increase in the release of dynorphin and cholecystokinin from the NIL, the increased secretion of these neuropeptides and P-endorphin may stimu late insulin secretion from the 'residual' pan creatic islets in streptozotocin-treated rats, as a compensatory mechanism for the decrease in insulin secretion. Opioid peptides [36] and cholecystokinin [37] have been shown to be insulinotropic when administered peripher ally.…”
Section: Discussionmentioning
confidence: 99%
“…Somehow, the anterior pituitary was not studied. Hollt et al [17], however, reported a decrease of leu-enkephalin in the neuro-intermediate lobe after adrenalectomy and an increase after dexamethasone treatment.…”
Section: Effect Of Corticosteroidsmentioning
confidence: 95%
“…The pituitary was divided into its AL and NIL component parts and the brain dissected to yield the hypothalamus, septum, midbrain and medulla/pons. Procedures for preparation of material for, and performance of, ra dioimmunoassays have been extensively described previously [13][14][15]22]. Owing to limitations in the amount of immunoreactive material in the septum and midbrain, it was impossible to deter mine the levels of each one of the peptides therein.…”
Section: Evaluation Of Levels O F Peptidesmentioning
confidence: 99%
“…Moreover, a variety of endocri nological manipulations have been documented to modu late, in parallel, neurointermediate lobe (NIL) concentra tions of ir-DYN and ir-VPin the rat [14].…”
mentioning
confidence: 99%